Creation of the Zahoransky Personal Nouns (case study of the novels by V. Lys «The Century of Jacob» and «Solo for Solomiya») (Linguostylistic Studies, 2018)
A characteristic feature of the proper names is their capacity to vary with a variety of word-building formants in everyday conversational speech. Quite often the same formants may be used for the creation of many or one-two variants of names in several localities. Creating variants of names is a unique original linguistic creativity of the people. Normally scholars analyze the features of the personal nouns of each locality using their own field records, but sometimes they study the linguistic phenomena using the artistic works, which describe the life of the people, living in a particular locality and epoch. The novels “The Century of Jacob” and “Solo for Solomiya” by V. Lys offer perfect materials for the case study.The article highlights the creation of the name variants used in the novels by V. Lys “The Century of Jacob” and “Solo for Solomiya” and their parallels in the Volyn-Polissian dialects. The study reports on the word-building analysis of the namespaces that appeared as a result of suffixation from the full and truncated/reduced forms of the official names with their various combinations. The study has revealed a group of proper names used only in the variant forms: Федь [Fed’] , Ганя [Hania], Гафія [Hafiia], Катя [Katia], Леся [Lesia], Нюра [Niura], Рипина [Rypyna] and some compound forms: Вікторія-Віка [Viktoria-Vika], Софійка-Зосечка [Sofijka-Zosechka], Зосечка-Зосина [Zosechka-Zosyna]. The variants of the personal names of Volyn Polissya residents have been revealed during expeditions in 48 settlements. 42 official male personal names and 41 female names were recorded. Among them 7 male and female names are fixed only in variants. Variants of the male names formed by means of the productive formants dominate. These are mainly the authentic Ukrainian suffixes (they are found both in the novels by V. Lys and in the colloquial speech of the Volyn Polissya). The most common formants of literary variants of male names are: -yk (-ik), -k-a,  -k-o, -uno, -us, -ts-o, -chyk, which create long word- formation rows, and female: -echk-a (-yechk-a), -enk-a, -k-a, -ochk-a, -un′-a, -us′-a, -ts′-a (-dz′-a), which are highly-productive or just productive among the residents of Volyn Polissya. Unproductive or low-productive literary word-formation types (8) are the names with suffixes in male names variants - ash, -echk-o, -o, -osh/-ish, -s, -ushk-a, -ts′, -shk-o. Low-productive word-building types (12) among women's/female names variants, which are also unproductive or low-productive in Volyn Polissya, are those with suffixes -akh-a, -echk-o, -yn-a, -ynk-a, -ys-a, -os-ya, -okh-a, -s-ya, -uk-a, -ul-ya, -ulk-a, -ushk-a.
Keywords: proper names; variants; word formation; productive and nonproductive suffixes